Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan - Septyarani, Tiara Azalia; Nurhadi, Nurhadi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2023)
The development of online businesses and the rapid use of E-Commerce has greatly affected the delivery of goods in Indonesia. Indonesian people currently entrust their goods to be sent through various expeditions that have been widely found. However, in the process of delivering goods, there are certainly some considerable obstacles such as delays in delivery, wrong delivery address, damaged or lost goods, and others that can make consumers' trust or attitude towards delivery services decrease. Therefore, Shopee began to establish its own logistics service that has been integrated with its services. This logistics service owned by Shopee is named Shopee Xpress which appeared in 2019. With its own logistics service, delivery will be more guaranteed because it is easy to be supervised by Shopee. This study aims to analyze the effect of service quality on customer loyalty through customer satisfaction as an intervening variable at the Shopee Xpress expedition. The population in this study were users of Shopee Xpress expedition services ranging in age from 15 to 54 years who were in the Surabaya City area, East Java. The questionnaire was distributed to people in the city of Surabaya, East Java who had made more than one use of the Shopee Xpress expedition service. A sample of 100 respondents was taken using purposive sampling technique. This study uses multiple linear regression techniques. The results showed that Service Quality has a significant positive effect on Customer Satisfaction. Likewise, Service Quality and Customer Satisfaction have a positive and significant effect on Customer Loyalty. The results of path analysis provide empirical evidence that the Customer Satisfaction variable acts as a partial mediating variable in bridging the effect of Service Quality on Customer Loyalty.